Preparation of PVDF membrane via synergistically vapor and non-solvent-induced phase separation - Min Chen; Qianyun Sun; Yue Zhou; Zhaoliang Cui; Zhaohui Wang; Weihong Xing (Applied Water Science, 2022)
Abstract Poly(vinylidene fluoride) (PVDF) ultrafiltration (UF) membrane was prepared by vapor and non-solvent-induced phase separation (VNIPS) process, and the relationships between preparation conditions, phase separation behaviors and membrane structures were discussed. The phase diagram was generated by cloud point titration, the effects of environmental relative humidity, air exposure time and casting solution temperature on the structure and performance of the resulted membrane were investigated. The addition of polyvinylpyrrolidone (PVP) additives to the casting solution made the system thermodynamically unstable and led the turbidity curve shift toward the solvent/non-solvent axis. The experimental results showed that both average pore size and porosity increased with higher relative humidity. When the relative humidity increased from 35 to 85%, the mean pore size increased from 35 to 70 nm. The effect of exposure time on membrane structure was related to the air environment. It was found that under low temperature and low humidity conditions, exposure time had little effect on membrane structure. When the relative humidity was 75%, the mean pore size and distribution increased with the exposure time extension from 1.0 to 30 s. The mean pore size of the membrane could be reduced by reducing the relative humidity. When the temperature of the casting solution increased, the membrane pore size reached maximum at 80 °C, and the spherulite on the surface of the membrane decreased. The spherulite morphology almost disappeared when the temperature of the casting solution reached 120 °C. In addition, with the increase in the casting solution temperature, large pores appeared in the sub-layer of the membrane, which gradually widened the pore distribution, leading to the decrease in the tensile strength. The preparation condition was optimized as low temperature of casting solution, low humidity and low temperature of the environment. The fabrication process showed the potential for scaling-up production of the PVDF UF membrane by the VNIPS technique.